Impact of dual organsim probiotics supplement on intake and milk yield during early, mid and late lactation in cows - SRINIVAS, BANDLA; SRINATH, M (The Indian Journal of Animal Sciences, 2016)
Study was conducted to evaluate the impact of dual organism probiotic supplement (DOPS) on different stages of lactation. Crossbred cattle (36) were divided into control (CG) and experimental (EG) groups with 6 cows each in early (calving to 100 d), mid (101 to 210 d) and late (211 to 305+ d) lactation. Straw intake in EG was improved in all stages of lactation compared to CG. CS intake in EG improved in early lactation by 4.8%. Although DM intake improved with DOPS, digestibility of nutrients did not change significantly. Milk yield in EG increased significantly in early (5%) and late lactation (47%) compared to CG. In contrary, mean 4% fat corrected milk (FCM) yield in EG in mid lactation reduced by 3% compared to CG. Unlike in early and mid lactation, milk fat (%) in late lactation increased significantly in EG compared to CG. SNF content in milk was below the standards for the cow milk in early lactation in CG which improved significantly in EG. Study concluded that DOPS improved straw intake and effective during early (up to 100 d) and late lactation (> 210 d).